Common Ownership of Public Goods - Halonen-Akatwijuka, Maija; PaÖlis, Evagelos (Journal of Economic Behavior & Organization, 2020)
We analyze ownership of public goods in a repeated game focusing on common ownership. Under common ownership an owner’s access to the public good cannot be restricted by other owners. We find that under common ownership both the value of the relationship and the gain from deviation are high. Common ownership can provide the best incentives for cooperation when the value of the public good cannot be increased much by maintenance investments or the maintenance costs are sufficiently convex. We argue that these conditions are satisfied in Ostrom’s field studies of irrigation systems and common lands.
Keywords: Public goods; Common pool resources; Property rights theory; Relational contracts